Exploiting hybrid decode-and-forward – amplify-and-forward in NOMA: an application to device-to-device networks. (6th May 2020) - Dang, Huu-Phuc; Nguyen, Minh-Sang V.; Do, Dinh-Thuan; Pham, Hong-Lien
A novel model regarding downlink cooperative non-orthogonal multiple access (NOMA) in device-to-device network will be investigated in this paper, especially combining amplify-and-forward (AF) and decode-and-forward (DF) to achieve a hybrid scheme. We consider a remarkable trade-off between outage performances and power allocation factors. Especially, we study a hybrid AF and DF scheme, namely HDAF scheme for NOMA as follows: 1) The proposed scheme applies the AF scheme when the signal-to-interference-plus-noise ratio (SINR) at the relay is below a predefined threshold such that the relay cannot successfully decode the signal; 2) On the other hand, when the SINR at the relay is greater than the predefined threshold, the system will be applied the DF scheme to decode the signal and then forwards it to the destination, i.e., avoids noise and interference amplification at the relay. An analytical expression of the outage probability of the hybrid HDAF NOMA is derived based on the outage probability function in AF and DF mode. Numerical results are provided to illustrate the influence of network parameters such as transmit power, power constraint, and link distances on the outage probability.